A Critical Review of “Intellectuals of Iran: Despair and Hope Narrations” Intellectual Ideology in the Sociology of Intellectuals of Iran - Abbas Khalaji (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This paper is intended to review an academic book through a critical-analytical approach. The book, “Intellectuals of Iran: Despair and Hope Narrations”, is a sociological one written as a textbook for students of different fields of social and political sciences in Iran and in the world along the course of the development of the intellectual movement in contemporary Iran. Accordingly, the writer has tried to criticize and evaluate different aspects of the book such as its form, method, and theoretical and scientific contents to find out whether it is worthy of being regarded as a source of political sociology of Iran or as a general source for interested people. This will also pinpoint its value for academic addressees. The book is generally a valuable one containing positive features. Nevertheless, there are formal and methodological deficiencies, as well as some theoretical and scientific inadequacies which will hopefully be resolved in further editions and will provide a suitable text for the students.